Mobile Application with AI Chatbot for Intelligent Tutoring in Communication - Melgarejo-Alcantara, Marllury (International Journal of Interactive Mobile Technologies (iJIM), 2026)
According to UNESCO, 14% of young people over the age of 15 lack basic literacy skills. In addition, UNICEF reports that 70% of children in low- and middle-income countries cannot understand simple text. In Latin America, the situation is critical, with 55% of students lacking basic reading skills. In response to this problem, a mobile application with an AI chatbot was developed for intelligent tutoring in communication, using the Mobile-D methodology. For its evaluation, criteria such as usability, technology, and innovation on the part of teachers and users, as well as accessibility, design, and security, were applied, obtaining an average on the Likert scale of 4.37 and 4.39, respectively. These results highlight the acceptance and effectiveness of the application, showing its potential to improve students’ communication and literacy skills.